When Penalty Fails: Modeling Contractual Misincentives With Evidence From Portugal ITO Agreements. (December 2022) - Nepomuceno, Thyago Celso Cavalcante; Nepomuceno, Késsia Thais Cavalcanti; Poleto, Thiago; de Carvalho, Victor Diogho Heuer; Costa, Ana Paula Cabral Seixas
A misincentive is characterized as an incentive producing the opposite effect of motivating or preventing some specific action. In some circumstances, contract penalties such as sanctions and fines on late delivery or low-quality software encourage the irregularities instead of preventing them from occurring. The present study models misincentive behaviors in Information Technology Outsourcing (ITO) transactions as a Principal-Agent problem. Considering the non-linear relationship in software vendors' cost structure and the client's sensitivity to the product/service quality and delivery time, we offer theoretical modeling elucidating the best responses on agreements under incomplete and asymmetric information. Some empirical evidence of contractual misincentives is reported in outsourcing arrangements between private institutions and public administrations in Portugal. The contracts were divided into three categories: pure contracts with no incentive clauses, contracts with no explicit monetary penalties, and contracts under explicit sanctions. The results suggest that the knowledge of the penalty reduces the Agent's uncertainty about the Principal's cost structure and might lead them to intentionally delay the delivery of the technology.